Strengthening the Role of Advocates in Providing Legal Assistance to Indonesian Society - Suparno Suparno; Qorib Qorib (Jurnal Indonesia Sosial Sains, 2024)
The role of Advocates in providing legal assistance to the community is regulated in Article 1 number 1 Chapter I of Law Number 16 of 2011 concerning Legal Aid, which states: "Legal Aid is a legal service provided by Legal Aid Providers free of charge to Legal Aid Recipients". Meanwhile, the recipients of legal aid here are impoverished people or people and Legal Aid Providers are Legal Aid Institutions or community organizations that provide legal aid services as described in Law Number 16 of 2011 concerning Legal Aid. According to Law Number 18 of 2003 Article 1 number 9, Chapter I provides the meaning that "Legal Aid is a legal service provided by Advocates free of charge to clients who cannot afford it". Legal aid can be provided to everyone without distinguishing a person's social status. This is like what exists in a legal state (rechtsstaat) where the state recognizes and protects the human rights of every individual. The state's recognition of individual rights implies inequality of standing before the law for all people. Article 28 D paragraph (1) of the 1945 Constitution reads, "Everyone has the right to recognition, guarantees, protection, and fair legal certainty as well as equal treatment before the law." Consequently, Advocates play an important role in upholding legal protection in society. Therefore, the role of Advocates must always be enhanced and supported by the government